Microsoft Windows security : essentials - Gibson, Darril (Indianapolis, Ind : Wiley, 2011)
Windows security concepts and technologies for IT beginners IT security can be a complex topic, especially for those new to the field of IT. This full-color book, with a focus on the Microsoft Technology Associate (MTA) program, offers a clear and easy-to-understand approach to Windows security risks and attacks for newcomers to the world of IT
"Exam 98-367"--Cover. Includes index.
IT
Keywords: Electronic data processing personnel -- Certification -- Study guides; Computer networks -- Examinations -- Study guides